"Like a ticking time bomb": the persistence of trauma in the HIV diagnosis experience among black men who have sex with men in New York City - Ofole Mgbako; Ellen Benoit; Nishanth S. Iyengar; Christopher Kuhner; Dustin Brinker; Dustin T. Duncan (BMC, 2020)
Abstract Background Black men who have sex with men (MSM) are disproportionately affected by HIV compared to almost every other demographic group in the country and have worse outcomes along the care continuum. Diagnosis is a critical juncture. This study aims to explore the impact and meaning of an HIV diagnosis for Black MSM, and how this has changed over time, both for the individual's experience living with HIV as well as for Black MSM in general. Methods From 2017 to 2018, we conducted in-depth interviews with 16 black MSM living with HIV in New York City diagnosed between 1985 and 2016. Results Inductive analysis of the qualitative data allowed three major themes to emerge: diagnosis trauma, lack of patient -centeredness in the healthcare system, and acceptance of HIV diagnosis over time. Conclusions This small pilot study signals that an HIV diagnosis experience possibly remains traumatic for black MSM even in the era of highly effective ART, and they often perceive a lack of patient-centeredness in the delivery of a new diagnosis. This has persisted over time. In most cases, black MSM in our sample overcame this trauma due to self-motivation, social support and seeking out and fostering trusting relationships with their HIV provider and the healthcare system.